OPTIMIZING THE USE OF ANTIMICROBIALS IN PEDIATRIC INFECTIONS: A SYSTEMATIC REVIEW OF CLINICAL AND NURSING STRATEGIES - Susiana Jansen; Fransiskus Samuel Renaldi; Elfira Awalia Rahmawati (Yayasan Adra Karima Hubbi, 2026)
Antimicrobial resistance (AMR) is a global health threat that significantly impacts the pediatric population, which has unique physiological characteristics and high susceptibility to irrational antibiotic use. This systematic review aims to synthesize scientific evidence on clinical and operational strategies for optimizing antimicrobial use in pediatric infections. A literature search was conducted in major international databases following PRISMA guidelines, with the inclusion of studies evaluating antimicrobial stewardship interventions, diagnostic stewardship, pharmacokinetic/ pharmacodynamic (PK/PD)-based precision dosing, and standardized clinical pathways. Results indicate that an integrated approach consistently reduces antibiotic consumption, improves adherence to clinical guidelines, accelerates time to optimal therapy, and maintains or improves clinical outcomes without increasing mortality. Integration of rapid diagnostic tests and biomarkers supports faster de-escalation of therapy, while model-informed precision dosing improves achievement of therapeutic targets in critically ill populations. Operational factors such as institutional leadership, multidisciplinary collaboration, standardized metrics monitoring, and digital technology support have been shown to strengthen program sustainability. Overall, optimizing antimicrobial use in pediatric infections requires a holistic systems approach to improve the quality of therapy while suppressing the development of global resistance.